2018
DOI: 10.1039/c8ta03501f
|View full text |Cite
|
Sign up to set email alerts
|

Photodecomposition and thermal decomposition in methylammonium halide lead perovskites and inferred design principles to increase photovoltaic device stability

Abstract: Strategies of how to mitigate photodegradation and thermal degradation processes are proposed in this work in order to further improve operational stability in hybrid perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
539
1
11

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 518 publications
(578 citation statements)
references
References 29 publications
27
539
1
11
Order By: Relevance
“…The generation of defects may take place not only during the perovskite synthesis processes, but also during the perovskite solar cell operation. For example, methylammonium lead iodide (MAPbI 3 ) undergoes photodecomposition and thermal degradation during solar cell operation . Two reaction pathways were identified for these degradation processes (Figure c).…”
Section: Defects In Metal Halide Perovskitesmentioning
confidence: 99%
“…The generation of defects may take place not only during the perovskite synthesis processes, but also during the perovskite solar cell operation. For example, methylammonium lead iodide (MAPbI 3 ) undergoes photodecomposition and thermal degradation during solar cell operation . Two reaction pathways were identified for these degradation processes (Figure c).…”
Section: Defects In Metal Halide Perovskitesmentioning
confidence: 99%
“…

Although impressive performance has been obtained, PSCs are still far from commercial or real-life availability due to serious issues such as toxicity [15,16] and poor stability to heat, [17] oxygen, [18] moisture, [19,20] electric field, [21] and light. [18,22] The toxic nature of hybrid organic-inorganic lead halide perovskites has been traced to the presence of Pb in its chemical composition. [15,16,[23][24][25] Pb 2+ readily dissolves in water (e.g., rain water) to form a toxic solution capable of causing serious environmental pollution, harmful to human beings and the ecosystem.

…”
mentioning
confidence: 99%
“…This work highlights the importance of the dynamical processes taking place after an I‐related defect is generated in MAPbI 3 . Qi and co‐workers proposed that the generation of I 2 would lead further to subsequent degradation in a cascade effect highlighting the importance of iodine management 79a,96. Recently, it was shown that I 2 generation is mediated by I i + /I i − defect pair (Figure c) .…”
Section: Defects and Interface Engineeringmentioning
confidence: 99%